Estrategias que permitan reducir la desintegración familiar y su incidencia en la deserción escolar en la Escuela de Educación Básica Rio Vinces del Recinto El Jobo parroquia Zapotal cantón Ventanas Provincia de Los Ríos. Periodo lectivo 2019-2020 - Moreno Filian, Greco Frank (2020)
The study on the effects generated by the Strategies that can reduce family disintegration and its incidence in school dropout at the Rio Vinces School of Basic Education in El Jobo Parish, Canton Zapotal Windows, Province of Los Ríos, for which a sample is required representative of students, teachers and parents to implement the field study and through this achieve the objectives. The present study determined the effects generated by family disintegration in students, in the same way identified the factors faced by students and verified how they cope with the family in their studies at home and inside the institutions, so that they are implemented Surveys of the educational community, in order to gather information regarding the variables of the object of study and in turn verify the research hypotheses. According to the results achieved through the field study, we identify that there are several factors that cause family breakdown, including; diseases, migration, divorce and depression in the face of the economic situation that, through households, is the product of unemployment; Alcoholism and family abuse, this is the absence of parents, who are not interested in the integral education of their children and what happens in their daily lives. The results involve the design and implementation of programs aimed at informing parents about the need to provide their children with a safe, stable and conflict-free family environment, which will be seriously affected in academic development, as well as in your personal relationships. From the study carried out, it is defined as the scope of the proposal, the need to improve relations between parents and children, for this way to positively influence the students and reduce the dropout rates.